Role of oxidative stress, adiponectin and endoglin in the pathophysiology of erectile dysfunction in diabetic and non-diabetic men - Trebatický, Branislav; Žitňanová, Ingrid; Dvořáková, Monika; Országhová, Zuzana; Paduchová, Zuzana; Ďuračková, Zdeňka; Breza, Ján; Muchová, Jana (Physiological research, 2019)
Erectile dysfunction (ED) and diabetes mellitus (DM) share common pathophysiological risk factors including endothelial dysfunction which together with hyperglycemia contribute to the increased oxidative/glycooxidative stress. A reduced NO concentration is insufficient for relaxation processes in the penis. Chronic inflammation and endoglin are involved in the regulation of endothelial function. Adiponectin from the adipose tissue has anti-inflammatory effects. Our study aimed to investigate the relation between erectile function in patients with and without DM and the oxidative stress, hormone adiponectin, and endothelial dysfunction marker endoglin. Men (n=32) with ED evaluated by the International Index of Erectile function (IIEF-5) questionnaire (17 without DM (NDM); 15 with type 2 diabetes mellitus (DM)) and 31 controls were included. Advanced glycation end products (AGEs), 8-isoprostanes (8-isoP), protein carbonyls, antioxidant capacity, adiponectin and endoglin were determined in the blood. DM patients compared to NDM patients and controls, had increased levels of glucose, C-reactive protein, triacylglycerols, 8-isoP, AGEs, endoglin and BMI. IIEF-5 score, NO and adiponectin levels were decreased. We are the first to find out that endoglin shows a negative correlation with erectile function in NDM, but not in DM patients. Endoglin can be considered as endothelial dysfunction marker in nondiabetic men suffering from ED.
Keywords: Endoglin; dospělí; endoglin; Diabetes Mellitus, Type 2; Oxidative Stress; lidé středního věku; Adiponectin; lidé; mužské pohlaví; Erectile Dysfunction; Male; adiponektin; oxidační stres; Middle Aged; diabetes mellitus 2. typu; erektilní dysfunkce; Adult; Humans